Identifikasi Salmonella Sp pada Jajanan Sosis yang Dijual di Kelurahan Harapan Baru Samarinda Seberang - Maryani, Pira; Makkadafi, Suparno Putera; Harlita, Tiara Dini (Universitas Malahayati, 2023)
ABSTRACT Sausages are one of the snacks that are in demand among the public, sausages are made from a mixture of ground meat and flour or starch. Sausage is fine meat that is processed with a mixture of herbs and spices which is then formed into a wrapper. The aim of this research is to determine the presence of contamination in sausages and identify Salmonella sp bacteria in sausage snacks sold in Harapan Baru Village, Samarinda Seberang. This research is a descriptive study, the sample used was 30 raw sausages taken by random sampling. The samples are then cultured to see whether there is bacterial contamination and identification to determine the presence of Salmonella sp. Data were analyzed univariately. Based on the results of research on 30 samples of sausage snacks, it was discovered that 7 samples were contaminated with bacteria. The identification results showed that there was no Salmonella sp bacterial contamination, but there were other bacteria, namely Enterobacter cloacae (3%) and Raoultella ornithinolytica (4%). It can be concluded that from the results of the identification of the presence of Salmonella sp from the 30 samples that have been studied, there was no contamination of Salmonella sp bacteria in the sausage snacks sold in Harapan Baru Village, Samarinda Seberang, but contamination of other bacteria was found, namely Enterobacter cloacae and Raoultella ornithinolytica bacteria as many as 7 (23%) contaminated samples. Based on the percentage results, it was found that 77% negative results for Salmonella sp bacteria in sausage snacks, so the results obtained did not meet the Indonesian National Standard SNI No. 3820:2015. Keywords: Sausage,Personal Hygiene, Salmonella sp ABSTRAK Sosis adalah salah satu jajanan yang diminati di kalangan masyarakat, sosis dibuat dari campuran daging halus dan tepung atau pati. Sosis merupakan daging halus yang diolah dengan campuran bumbu dan rempah-rempah yang kemudian dibentuk dalam pembungkus. Tujuan penelitian ini untuk mengetahui adanya kontaminasi pada sosis dan mengidentifikasi bakteri Salmonella sp pada jajanan sosis yang dijual di Kelurahan Harapan Baru Samarinda Seberang. Penelitian ini merupakan penelitian deskriptif, sampel yang digunakan adalah 30 buah sosis mentah yang diambil secara random sampling. Sampel kemudian dikultur untuk melihat ada tidaknya kontaminasi bakteri dan identifikasi untuk mengetahui keberadaan Salmonella sp. Data dianalisis secara univariat. Berdasarkan hasil penelitian pada 30 sampel jajanan sosis, diketahui bahwa terdapat 7 ssampel yang terkontaminasi bakteri. Hasil identifikasi menunjukkan tidak adanya cemaran bakteri Salmonella sp, namun terdapat bakteri lain yaitu Enterobacter cloacae (3%) dan Raoultella ornithinolytica (4%). Dapat disimpulkan bahwa dari hasil identifikasi keberadaan Salmonella sp dari 30 sampel yang telah diteliti tidak ditemukan adanya cemeran bakteri Salmonella sp pada jajanan sosis yang di jual di Kelurahan Harapan Baru Samarinda Seberang, tetapi ditemukan kontaminasi cemaran bakteri lain yaitu bakteri Enterobacter cloacae dan Raoultella ornithinolytica sebanyak 7 (23%) sampel yang terkontaminasi. Berdasarkan hasil presentase didapatkan 77% hasil negatif bakteri Salmonella sp pada jajanan sosis, maka dari hasil yang telah didapatkan tidak memenuhi Standar Nasional Indonesia SNI No. 3820:2015. Kata Kunci : Sosis,Personal Hygiene, Salmonella sp